BOTTOM-UP CLIMATE VILLAGE PROGRAM FOR COMMUNITY PARTICIPATION IN CLIMATE ACTION: A CASE STUDY OF SAMBAK VILLAGE, MAGELANG - Kurniasih, Yuni; Winanta, Rizza Arge; Mali, Matheus Gratiano (Dinamika Governance: Jurnal Ilmu Administrasi Negara, 2025)
This study examines the role of community participation in the implementation of the Climate Village Program (ProKlim) in Sambak Village, Kajoran Sub-District, Magelang Regency, Indonesia. Using Cohen and Uphoff's (1980) framework, it evaluates participation in decision-making, implementation, benefit-sharing, and evaluation. The study adopts a descriptive qualitative research design, incorporating primary data from observations, interviews, and documentation, and secondary data from relevant literature and reports. Data collection employs purposive sampling, targeting informants such as village leaders, ProKlim coordinators, and community members. Data analysis follows Miles and Huberman's interactive model, including reduction, presentation, and conclusion drawing, validated through triangulation methods. The findings reveal varying levels of community engagement across these areas. While waste management activities see high participation, food security and conservation initiatives face challenges due to limited awareness, work commitments, and perceived benefits. Internal evaluations feature active feedback, but external evaluations lack broader community involvement due to ineffective communication. The study highlights the importance of enhancing community engagement to ensure the program's sustainability and alignment with Sustainable Development Goal (SDG) 13 on Climate Action. Recommendations are provided to address barriers and optimize participatory strategies, contributing to the broader effectiveness of grassroots climate initiatives.